Healing of diabetic cutaneous wound mediated by small extracellular vesicles derived from mesenchymal stem cells - Tianyi Li; Wenting Zhang; Yingjie Sun; Xianbin Zeng; Yuhui Sun; Gang Ding (Oral Science and Homeostatic Medicine, 2026)
Abstract Diabetic cutaneous wounds, particularly diabetic foot ulcers, are among the most severe chronic complications of diabetes mellitus and remain a major clinical challenge because of persistent inflammation, oxidative stress, impaired angiogenesis, and delayed tissue regeneration. Although conventional therapies such as debridement, infection control, and growth factor application can partially improve wound conditions, their overall efficacy remains limited. Mesenchymal stem cell-derived small extracellular vesicles (MSC-sEVs) have recently emerged as a promising cell-free therapeutic strategy for diabetic wound repair. Increasing evidence indicates that MSC-sEVs can regulate multiple pathological processes involved in diabetic wounds, including macrophage polarization, neutrophil extracellular trap formation, oxidative stress, ferroptosis, cellular senescence, and autophagy dysfunction. Through these mechanisms, MSC-sEVs promote angiogenesis, collagen deposition, fibroblast proliferation, keratinocyte migration, and re-epithelialization, thereby accelerating wound closure and tissue regeneration. This review summarizes recent advances in MSC-sEV-based diabetic wound therapy by linking major pathological barriers with specific cellular targets and molecular mechanisms, thereby highlighting the mechanistic basis and potential advantages of MSC-sEVs over conventional cell-based strategies. Current limitations, including heterogeneity of MSC sources, insufficient standardization of sEV isolation and characterization, limited retention at wound sites, and incomplete clinical validation, are also discussed. Future research should focus on standardized production, functional engineering, carrier-based delivery systems, and well-designed preclinical and clinical studies to facilitate the cautious and evidence-based translation of MSC-sEVs for chronic diabetic wound management.